2019
DOI: 10.1177/0091026019878210
|View full text |Cite
|
Sign up to set email alerts
|

Veterans and Job Satisfaction in the U.S. Federal Government: The Importance of Role Clarity in the First Years of Civilian Employment

Abstract: Veterans can face difficulties adjusting to civilian employment due to their experiences in highly structured and regimented military service organizations. This study focuses on factors that affect the job satisfaction of veterans employed in the civilian U.S. Federal Government. Drawing on sector imprinting theory, we propose that role clarity will have a stronger link with job satisfaction for government employees who have served in the military than for those who have not. Second, we argue that this differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…For example, Olmstead (2011) found that veterans had higher job satisfaction when compared to non-veterans in civilian organizations However, Van Maanen (1975) and Zangaro and Johantgen (2009) found that police recruits who had military experience initially reported having higher motivation, commitment, and satisfaction when compared to officers without military experience, but these differences faded as their years of experience increased. Along these same lines, Zangaro and Johantgen (2009), Teclaw et al (2016), andCampbell (2020) found that non-veterans reported significantly higher job satisfaction than veterans in civilian government work settings.…”
Section: Comparative Research In Civilian Organizationsmentioning
confidence: 78%
“…For example, Olmstead (2011) found that veterans had higher job satisfaction when compared to non-veterans in civilian organizations However, Van Maanen (1975) and Zangaro and Johantgen (2009) found that police recruits who had military experience initially reported having higher motivation, commitment, and satisfaction when compared to officers without military experience, but these differences faded as their years of experience increased. Along these same lines, Zangaro and Johantgen (2009), Teclaw et al (2016), andCampbell (2020) found that non-veterans reported significantly higher job satisfaction than veterans in civilian government work settings.…”
Section: Comparative Research In Civilian Organizationsmentioning
confidence: 78%
“…The perceived congruence of individual and organizational values at the heart of fit can change over time, and thereby value congruence will likewise fluctuate (Gabriel et al, 2014). This plasticity is leveraged by some organizations, such as those associated with the armed forces, to facilitate fit through training and socialization (Tao and Campbell, 2020). However, because values and goals are socially constructed to some extent, we suggest that ER 43,4 OSC may enhance P-O fit.…”
Section: The Mediating Role Of Person-organization Fitmentioning
confidence: 87%
“…The quantitative method examines the narrowly defined research questions by utilizing a scientific method to select samples and collect data from a population, and a statistical method to analyze data, and generalize findings to a larger population (Borrego et al, 2009). Additionally, previous researchers have demonstrated that a quantitative method is appropriate in investigating the relationship between motivation, job satisfaction, and job design (Al-Musadieq et al, 2019;Edinger & Edinger, 2018;Nowlin et al, 2018;Tao & Campbell, 2020;Westover et al, 2020). As such, a quantitative method was an appropriate method for the study.…”
Section: Methodsmentioning
confidence: 99%